Some marxian and smithian ideas on labor and prices. (2013)
The propositions advanced by Marx and Smith on the relation between labor and prices are examined, with particular emphasis on income distribution, within a non-Walrasian setting including joint production and heterogeneous labor. Among its contributions, the paper introduces the concept of indirect joint production and an alternative definition of industrial branches.